Diagnóstico de gerenciamento de resíduos de serviços de saúde gerados em laboratórios de ensino e de pesquisa da Universidade Federal de São Carlos – campus de São Carlos - SP - Teixeira, Aline Pialarici (Universidade Federal de São Carlos, 2020)
The teaching and research laboratories of the Higher Education Institutions (HEI) contribute with a significant share in the generation of Health Services Waste (HSW). This study aimed to perform a diagnosis on the management of the HSW generated in teaching and research laboratories of the Federal University of São Carlos (UFSCar), São Carlos Campus. It is an exploratory and descriptive field research, using quantitative variables. The research was carried out in 168 teaching and research laboratories of the Biological Sciences and Health Center (BSHC) and the Exact Sciences and Technology Center (ESTC) of UFSCar. 168 people who were in charge for the laboratories participated in the survey. The data were collected through a self-respond questionnaire, using an instrument adapted from Veiga (2011). Data collection began after the approval of the Research Ethics Committee (REC) of UFSCar. The data was analyzed by means of descriptive statistics. The results showed that the UFSCar laboratories generate HSW of Groups A, B, C, D and E. It is noteworthy that 33.8% of the laboratories generated biological waste, 67.9% chemical waste and 59.5% perforating waste. Regarding the segregation, 73.2% of the laboratories segregated biological waste, 76.5% and 86%, respectively, segregated chemical waste and perforating waste. As for stowage, 66.1% of the laboratories stowaged the biological waste in identified containers, 89.9% and 77%, respectively, of the laboratories that generated chemical waste and perforating agents stowaged the waste in identified containers. Furthermore, in 72.5% of the laboratories, the residues were transported manually; 39.3% of the laboratories did not have an exclusive place to store the HSW. Regarding the treatment of HSW, in 27% of the laboratories, the biological waste was submitted to autoclave treatment, in 18% 7.9% of the laboratories the chemical waste and perforating agents were incinerated, and in 4.3% the common waste was sent for recycling. In addition, 32.8% of those responsible did not know how the external collection was performed; and, 77% did not know the type of final disposal. As for the reuse and recycling actions, 41.1% stated that the common waste was recycled; still, 82.1% of the laboratories did not have HSWMP and 83.3% of the laboratories that had the plan did not use standards for its construction. It is considered that the management of HSW in the teaching and research laboratories of BSHC and ESTC of UFSCar is being carried out adequately; however, it has gaps in relation to the knowledge of participants about the management of HSW. The need to build a HSWMP is highlighted, as well as the development of permanent education programs, focusing on chemical residues, in order to improve the knowledge of the academic population, user of these laboratories.

Los laboratorios de enseñanza e investigación de las Instituciones de Enseñanza Superior (IES) contribuyen con una parte significativa en la producción de Residuos de Servicios de la Salud (RSS). Este estudio tuvo como objetivo realizar un diagnóstico sobre el gerenciamiento de los RSS producidos en laboratorios de enseñanza e investigación de la Universidad Federal de São Carlos (UFSCar), Campus São Carlos. Se trata de una investigación de campo, de carácter exploratorio y descriptivo, utilizando variables cuantitativas. La investigación fue realizada en 168 laboratorios de enseñanza e investigación del Centro de Ciencias Biológicas y de Salud (CCBS) y del Centro de Ciencias Exactas y de Tecnología (CCET) da UFSCar. Participaron de la investigación 168 responsables por los laboratorios. Los datos fueron recolectados por medio de un cuestionario auto respondido, utilizando un instrumento adaptado de Veiga (2011). La recolección de datos se inició después de la aprobación del Comité de Ética en Investigación (CEP) de la UFSCar. Los datos fueron analizados por medio de la estadística descriptiva. Los resultados mostraron que los laboratorios de la UFSCar producen RSS de los Grupos A, B, C, D y E. Se destacan que 33,8% de los laboratorios producían residuos biológicos, 67,9% residuos químicos y 59,5% residuos perforo-colorantes. En relación a la segregación, 73,2% de los laboratorios realizaban la segregación de los residuos biológicos, 76,5% y 86%, respectivamente, segregaban los residuos químicos y perforo-colorantes. En cuanto al acondicionamiento, 66,1% de los laboratorios acondicionaban los residuos biológicos en recipientes identificados, 89,9% y 77%, respectivamente, de los laboratorios que producían residuos químicos y perforocolorantes acondicionaban los residuos en recipientes identificados. Aún, en 72,5% de los laboratorios los residuos eran transportados manualmente; 39,3% de los laboratorios no poseían un local exclusivo para el almacenamiento de los RSS. En lo que se refiere al tratamiento de los RSS, en 27% de los laboratorios los residuos biológicos eran sometidos al tratamiento por autoclave, en 18% 7,9%, respectivamente, de los laboratorios los residuos químicos y perforo-colorantes eran incinerados, y, en 4,3% los residuos comunes eran enviados para reciclaje. También, 32,8% de los responsables no sabían como la recolección externa era realizada; y, 77% desconocían el tipo de disposición final. En cuanto a las acciones de reaprovechamiento y reciclaje, 41,1% afirmaron que los residuos comunes eran reciclados; todavía, 82,1% de los laboratorios no poseían PGRSS y 83,3% de los laboratorios que poseían el plan, no utilizaron normas para a su construcción. Se considera que el manejo de los RSS en los laboratorios de enseñanza e investigación del CCBS y CCET de la UFSCar está siendo realizado de forma adecuada; sin embargo, presenta carencias en relación al conocimiento de los participantes sobre el manejo de los RSS. Se destaca la necesidad de construcción de un PGRSS, bien como el desenvolvimiento de programas de educación permanente, con enfoque en los residuos químicos, a fin de mejorar el conocimiento de la población académica, usuaria de esos laboratorios.
Diagnosis of management of Health Services Waste generated in teaching and research laboratories of the Federal University of São Carlos - campus of São Carlos - SP
Diagnóstico de gerenciamiento de Residuos de Servicios de Salud producidos en laboratorios de enseñanza y de investigación de la Universidad Federal de São Carlos – campus de São Carlos – SP
Keywords: Resíduos sólidos urbanos; Resíduos de serviços de saúde; Gerenciamento de resíduos; Laboratórios; Educação superior; Urban solid waste; Health services waste; Waste management; Laboratories; Higher education; Residuos de servicios de salud; Laboratorios; Educación superior; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS